2002
DOI: 10.1163/156856202320269157
|View full text |Cite
|
Sign up to set email alerts
|

Novel dendrimer based polyurethanes for PEO incorporation

Abstract: A series of segmented polyurethanes based on methylene diisocyanate/poly (tetramethylene oxide) and chain extended with either ethylene diamine or butane diol in combination with a generation 2 polypropylenimine octaamine dendrimer were synthesized. For polymer synthesis, the dendrimers were protected with either t-boc or Fmoc groups and were incorporated into the polyurethane microstructure to permit further functionalization with biologically active groups. Following deprotection, the dendrimers were reacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…While further testing of these HA-modified materials will be needed in order to verify their potential for use in vascular applications, the in vitro tests reported herein have been promising, demonstrating the ability of PU grafted with low molecular weight HA to reduce protein adsorption and platelet adhesion while promoting endothelialization and retaining vascular-appropriate mechanics. A number of different methods can be used to introduce functional groups to PU, such as functionalization of the bulk material or surface activation with various reactive monomers [32]. Surface modification methods are usually based on radiofrequency-generated gas plasmas [29], but the plasma-treated surfaces become unstable upon exposure to air and experience rapid changes in their surface characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…While further testing of these HA-modified materials will be needed in order to verify their potential for use in vascular applications, the in vitro tests reported herein have been promising, demonstrating the ability of PU grafted with low molecular weight HA to reduce protein adsorption and platelet adhesion while promoting endothelialization and retaining vascular-appropriate mechanics. A number of different methods can be used to introduce functional groups to PU, such as functionalization of the bulk material or surface activation with various reactive monomers [32]. Surface modification methods are usually based on radiofrequency-generated gas plasmas [29], but the plasma-treated surfaces become unstable upon exposure to air and experience rapid changes in their surface characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrimers have been studied as gene (Haenseler and Szoka (1993); Kukowska-Latallo et al, (1996); Bielinska et al, (1997); Bielinska et al, (1999); Bielinska et al, (2000)) and drug delivery (Barth et al, (1994); Kono et al, (1999); Liu et al, (2000); ; ) vehicles, as well as for cellular recognition, cell adhesion and cell growth regulation (Zanini et al (1995); Zanini and Roy (1997); Kawase et al (2001)). They have also been used for the modification of biologically relevant polymeric materials to increase the density of relevant functional groups (Duan et al (2002)). These studies suggest that dendrimers are generally biologically acceptable, which is thought to be due in part to the similarity of their size and shape to many biological components.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers have been shown to modify gold surfaces and these surfaces have been suggested to have various applications (Rahman et al (2000); Zhao et al (1999); Tokuhisa et al, (1998);Liu et al (1997)). We have previously demonstrated that dendrimers can be incorporated into the structure of polyurethanes and polyurethane ureas and can be subsequently functionalized with polyethylene oxide (PEO) chains (Duan et al (2002)). The incorporation of a relatively small amount of dendrimer into the polyurethane structure during the chain extension step and its subsequent functionalization with PEO resulted in a significant (40%) decrease in the adsorption of fibrinogen and decreases in the adsorption of other plasma proteins.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the second route described by Kumar and Ramakrishnan [38] employed an isocyanate-free approach to synthesize polyurethane dendrimers. Following these pioneering works, a few more dendritic polyurethanes have been reported [39][40][41][42][43][44][45][46]. More recently, Nasar and coworkers have reported the synthesis of hyperbranched polyurethanes and polyurethane dendrimers based on blocked isocyanate chemistry [47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…First reported by Hawker and Fréchet for the synthesis of poly(phenyl benzyl ether) dendrimers, ref [54] the convergent method ensures the precise placement of functional groups throughout the dendritic structure that enables the synthesis of functional macromolecules. Though several dendrimers are reported recently employing the convergent method of synthesis, refs [21,24,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] there are very few reports on polyurethane dendrimers using this method [40,[73][74][75].…”
Section: Introductionmentioning
confidence: 99%